The sweet side of global change–dynamic responses of non-structural carbohydrates to drought, elevated CO2 and nitrogen fertilization in tree species. (11th June 2018) - Li, Weibin; Hartmann, Henrik; Adams, Henry D; Zhang, Hongxia; Jin, Changjie; Zhao, Chuanyan; Guan, Dexin; Wang, Anzhi; Yuan, Fenghui; Wu, Jiabing
Abstract: Non-structural carbohydrates (NSC) play a central role in plant functioning as energy carriers and building blocks for primary and secondary metabolism. Many studies have investigated how environmental and anthropogenic changes, like increasingly frequent and severe drought episodes, elevated CO2 and atmospheric nitrogen (N) deposition, influence NSC concentrations in individual trees. However, this wealth of data has not been analyzed yet to identify general trends using a common statistical framework. A thorough understanding of tree responses to global change is required for making realistic predictions of vegetation dynamics. Here we compiled data from 57 experimental studies on 71 tree species and conducted a meta-analysis to evaluate general responses of stored soluble sugars, starch and total NSC (soluble sugars + starch) concentrations in different tree organs (foliage, above-ground wood and roots) to drought, elevated CO2 and N deposition. We found that drought significantly decreased total NSC in roots (−17.3%), but not in foliage and above-ground woody tissues (bole, branch, stem and/or twig). Elevated CO2 significantly increased total NSC in foliage (+26.2%) and roots (+12.8%), but not in above-ground wood. By contrast, total NSC significantly decreased in roots (−17.9%), increased in above-ground wood (+6.1%), but was unaffected in foliage from N fertilization. In addition, the response of NSC to three global change drivers was strongly affected by tree taxonomic type, leaf habit, tree age and treatment intensity. Our results pave the way for a better understanding of general tree function responses to drought, elevated CO2 and N fertilization. The existing data also reveal that more long-term studies on mature trees that allow testing interactions between these factors are urgently needed to provide a basis for forecasting tree responses to environmental change at the global scale.